2018
DOI: 10.1016/j.bpj.2018.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Collective Cell Behavior in Mechanosensing of Substrate Thickness

Abstract: Extracellular matrix stiffness has a profound effect on the behavior of many cell types. Adherent cells apply contractile forces to the material on which they adhere and sense the resistance of the material to deformation-its stiffness. This is dependent on both the elastic modulus and the thickness of the material, with the corollary that single cells are able to sense underlying stiff materials through soft hydrogel materials at low (<10 μm) thicknesses. Here, we hypothesized that cohesive colonies of cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…The crosslinking method did not seem to make any difference in this case, and there was no obvious difference compared to the untreated films as well. When a cell adheres to a substrate it responds to the substrate stiffness through the rearrangement of the cytoskeletal components such as actin filament and microtubules . Cells have more organized cytoskeletons on stiffer substrates .…”
Section: Resultsmentioning
confidence: 99%
“…The crosslinking method did not seem to make any difference in this case, and there was no obvious difference compared to the untreated films as well. When a cell adheres to a substrate it responds to the substrate stiffness through the rearrangement of the cytoskeletal components such as actin filament and microtubules . Cells have more organized cytoskeletons on stiffer substrates .…”
Section: Resultsmentioning
confidence: 99%
“…ASCs cultured on TCP are expected to have a spindle‐shaped morphology, with cell spreading and flattening serving as markers of senescence in long‐term culture . In general, cell spreading varies in 2D and 3D systems, and correlates with properties such as substrate stiffness, ligand density, and arrangement through the regulation of focal adhesions . As such, the spindle‐shaped morphology observed on the α‐amylase‐digested coatings may be related to their lower stiffness and more fibrous 3D ultrastructure .…”
Section: Discussionmentioning
confidence: 99%
“…In general, cell spreading varies in 2D and 3D systems, and correlates with properties such as substrate stiffness, ligand density, and arrangement through the regulation of focal adhesions . As such, the spindle‐shaped morphology observed on the α‐amylase‐digested coatings may be related to their lower stiffness and more fibrous 3D ultrastructure . Fibrous topographies have been postulated to provide cells with a greater local surface area with multiple physical sites for engraftment in all three dimensions, favorable for cell attachment, migration, and proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…al. showed that the cell colonies can sense the underlying rigid material through a 200 µm thick soft gel, the thickness through which a single cell cannot sense the underlying rigid material 25 . However, while they used cell colonies, we showed that single cells in close vicinity to each other can sense the embedded rigid structure from far away distance due to relay of the strain field via collective traction.…”
Section: Discussionmentioning
confidence: 99%
“…As the stiffness of the PAA gel increases the zone of deformation of PAA gel due to force applied by cells decreases 26,27 . Also, the depth sensing ability of collective cell is less than 200 µm 25 . Therefore, when the stiffness of PAA gel or top layer of PAA gel was increased, the patterning disappeared.…”
Section: Discussionmentioning
confidence: 99%